Persepsi Gen Z terhadap Koperasi Sebagai Entitas Bisnis yang Berkelanjutan - Mujiyanti, Sri Ayudha; Maulidiyah, Nailin Nikmatul; Dassucik; Rasyidi, Ahmad Hafas; Indawati, Nindi Kamila (Jurnal Informatika Ekonomi Bisnis, 2023)
Cooperatives are collaborative organizations that stand between commercial businesses and cooperatively managed resources. The cooperative business model is a sustainable business. Gen Z is the next generation of future owners who need to know about the advantages of the cooperative business model. In this study, knowledge is the only variable studied to prove whether this factor has an impact to perception.